2021
DOI: 10.11152/mu-3149
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ultrasound examination in atypical placental site trophoblastic tumour differential diagnosis and management. A case report

Abstract: Placental site trophoblastic tumour (PSTT) is a very rare and unique form of gestational trophoblastic tumour, representing about 1-2% of all gestational trophoblastic tumours. Usually, the pattern is a slow growing nodule implicating the endometrium and myometrium, accompanied by abnormal uterine bleeding. Three ultrasound types of PSTT are described, but thereis no specific characteristic for diagnosis. We present the case of a patient with an atypical placental site trophoblastic tumour diagnosed two months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The diagnostic criteria for APSN have not yet been defined in the latest guidelines for the management of GTD [ 1 ]. APSN is seldom reported, and it is located in the endometrium of the uterine body and has not invaded the myometrium mostly in the related literature [ 8 , 9 ]. In this study, we report a case of APSN located in the uterine diverticulum after cesarean section, which was misdiagnosed as intrauterine residue, and we found that this case of APSN invaded the myometrium of the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria for APSN have not yet been defined in the latest guidelines for the management of GTD [ 1 ]. APSN is seldom reported, and it is located in the endometrium of the uterine body and has not invaded the myometrium mostly in the related literature [ 8 , 9 ]. In this study, we report a case of APSN located in the uterine diverticulum after cesarean section, which was misdiagnosed as intrauterine residue, and we found that this case of APSN invaded the myometrium of the uterus.…”
Section: Introductionmentioning
confidence: 99%